Auditoría de gestión y su incidencia en la rentabilidad de Avícola Fernández S. A., del cantón Guayaquil, año 2014. - Tello León, Paulina de las Mercedes (2015)
The present management audit was conducted at the Poultry Company Fernández SA, Guayaquil distrit. Guayas province, the owner Fernández Eugenio de Jesús Zambrano, from the outset affirmed its core business in breeding, slaughter and sale of meat products, particularly chicken hence its name, and later decided to expand product sales staples, same that you are listed in the National Register of Taxpayers and the Companies Registry. The matrix is located in the Cdla. The Garzota Mz. 149 Solar # 9, a few meters from the bus station of the city, its activities are initiated about 20 years ago but from July 24, 2000, which was established as a company according to its charter, has a term duration of 50 years from October 10, 2000, date on which it was entered in the Trade Register. The company is divided into 6 areas or managements and members of the same areas and workers or their staff will our study population. The proposed targets are closely linked to business requirements regarding the conduct of the audit, analysis of the organizational structure and policies of the company, evaluation of internal control, the application of financial indicators and the correct preparation of the report audit. The methodology used is based on the development of audit phases, where Phase I: Preliminary proceed to the knowledge of the history of the company; Phase II: Planning the audit planning and methodology developed are determined to follow. Now in Phase II, it runs, tabulates and analyzes the internal control relevant to the areas of the company by COSO method, what a result that areas are at a risk level between 76% was obtained - 95% determining that is a high standard. Management indicators applied to measure management within the company and the rates of return and may observe the effect on the latter. In the final part it is issued in a final report of findings and others for minor concerning the company.